WE WILL TAKE CARE OF YOU’: IDENTITY CATEGORIZATION MARKERS IN AN INTERVIEW WITH TRANSGENDER INDIVIDUAL - Kalsoom Jahan; Zahir ul Islam Hashmi; Hassan Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
This current research has systematically investigated discursive practices of categorization, examining the various ways in which social actors ascribe identity categories to themselves and others to accomplish diverse social actions. Drawing on data from an interview with transgender persons discussing their everyday experiences, along with a transcription of the video "A Trans ’Mother’ Debates Matt Walsh On Womanhood," the present work analyzes how participants invoke and make relevant social identity categories through the use of collective pronouns and other lexical choices. Our results showed that while institutional identities (e.g., those of support groups, community organizations, or social networks) were prominent, categorial formulations related to gender identity were frequently foregrounded, especially in interactions involving transgender participants. The inclusion of the video debate added a unique dimension, highlighting how gender identity categorizations are negotiated in more adversarial or public discourse settings. Conversational participants often engaged in complex negotiations of their gender identity, using these categorizations for rhetorical and pragmatic purposes, such as establishing solidarity, asserting agency, and negotiating epistemic authority. This study demonstrates how even minimal lexical choices, such as marked pronouns, significantly impact the negotiation of meanings and social dynamics, particularly for marginalized groups such as transgender individuals.